Motional narrowing effects in the excited state spin populations of Mn-doped hybrid perovskites - Zerhoch, Jonathan; Bodnar, Stanislav; Lerpinière, James E.; Liu, Shangpu; Neumann, Timo; Sergl, Barbara; Heindl, Markus W.; Shcherbakov, Andrii; Elghandour, Ahmed; Klingeler, Rüdiger; Walker, Alison B.; Deschler, Felix (The journal of physical chemistry letters, 2024)
Spin-orbit coupling in the electronic states of solution-processed hybrid metal halide perovskites forms complex spin-textures in the band structures and allows for optical manipulation of the excited state spin-polarizations. Here, we report that motional narrowing acts on the photoexcited spin-polarization in CH3NH3PbBr3 thin films, which are doped at percentage-level with Mn2+ ions. Using ultrafast circularly polarized broadband transient absorption spectroscopy at cryogenic temperatures, we investigate the spin population dynamics in these doped hybrid perovskites and find that spin relaxation lifetimes are increased by a factor of 3 compared to those of undoped materials. Using quantitative analysis of the photoexcitation cooling processes, we reveal increased carrier scattering rates in the doped perovskites as the fundamental mechanism driving spin-polarization-maintaining motional narrowing. Our work reports transition-metal doping as a concept to extend spin lifetimes of hybrid perovskites.